VIABILITAS BENIH ROSELA (Hibiscus sabdariffa L.) PADA BERBAGAI KADAR AIR AWAL DAN KEMASAN BENIH - Herri Wiliam Suhendra Purba; Ferry Ezra Sitepu; Haryati Haryati (Universitas Sumatera Utara, 2013)
The aim of the research was to studyseed viability of rosela (Hibiscus sabdariffa L.) during 3 months storage on various levels of initial seed moisture content and storage seed packaging. It was conducted in the Laboratory of Seed Technology, Faculty of Agriculture USU about 25 m sea level rise on Mei to September 2012 by using randomized block design with two factors. The first factor was various levels of initial moisture content(7%, 9% and 11%) and the second one was storage seed packaging(aluminium foil, polyethylene plastic and paper). Variables measured include moisture content, germination rate, grow potential, germination percentage and vigor index. The results showed that initial seed moisture contentshowed only significant effects on moisture content and storage seed packaging showed significant effects on moisture content, grow potential, and germination percentage. Interaction of both treatments showed non significant effect on all parameters. Key words : Rosela seed, moisture content, storage seed packaging and seed viability.